EVALUASI PEMANFAATAN ONLINE PUBLIC ACCESS CATALOG (OPAC) DI PERPUSTAKAAN UNIVERSITAS UDAYANA - Ni Nyoman Sutarini Sutarini; Ni Putu Premierita Haryanti; Ketut Ayu Sanjiwani (D3 Perpustakaan FISIP UNUD, 2025)
This study aims to evaluate the utilization of the Online Public Access Catalog (OPAC) at Udayana University Library and identify the factors that influence it. This study uses a qualitative method with descriptive research and the Unified Theory of Acceptance and Use of Technology (UTAUT) analysis model, which includes four indicators: performance expectancy, effort expectancy, social influence, and facilitating conditions. Data were collected through observation, in-depth interviews with five informants (four students as primary informants, and one librarian as supporting informant), and documentation. The results show that the OPAC provides convenience and efficiency in information retrieval, but has not been optimally utilized by all users. Factors such as ease of use, perceived benefits, the influence of the surrounding environment, and the availability of technical facilities and librarian assistance also influence OPAC utilization. There is a lack of direct guidance from librarians, especially new students. Increased training and socialization are needed to encourage maximum utilization of the OPAC in supporting the information needs of the academic community at Udayana University Library.